1998
DOI: 10.1101/gad.12.14.2102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel class of genomic DNA-binding sites suggests a mechanism for selectivity in target gene activation by the tumor suppressor protein p53

Abstract: There are two response elements for p53 in the promoter of the gene for the cyclin-dependent kinase inhibitor p21. The binding of p53 to the 5 site was enhanced by incubation with monoclonal antibody 421, whereas the binding of p53 to the 3 site was inhibited. Mutational analysis showed that a single-base change caused one element to behave like the other. A response element in the human cdc25C promoter is bound by p53 with properties similar to the 3 site. These results identify two classes of p53-binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
83
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 29 publications
10
83
1
Order By: Relevance
“…It is well demonstrated that p53 has different affinities for distinct p53REs, which would allow the p53 transcriptional program to be modulated by the nuclear concentration of p53 (Resnick-Silverman et al, 1998;Szak et al, 2001). At low concentrations of p53, only target genes carrying high affinity p53REs would be regulated.…”
Section: Keyword: Affinitymentioning
confidence: 99%
“…It is well demonstrated that p53 has different affinities for distinct p53REs, which would allow the p53 transcriptional program to be modulated by the nuclear concentration of p53 (Resnick-Silverman et al, 1998;Szak et al, 2001). At low concentrations of p53, only target genes carrying high affinity p53REs would be regulated.…”
Section: Keyword: Affinitymentioning
confidence: 99%
“…Additional reporter constructs used included: 1.5 kb TRAIL-promoter-Luc [22], 1 kb cFLIP-promoter-Luc [23,24] and p53RE-Luc [25]. Transient transfection of different reporter constructs (1 μg) together with pCMV-βgal (0.25μg) into 5×10 5 melanoma cells was performed using Lipofectamine (Life Technologies-Invitrogen).…”
Section: Transfection and Luciferase Assaymentioning
confidence: 99%
“…8,9 Sequence-specific binding of wild-type p53 to p53 response elements (p53REs) within the DNA is essential for its role as a tumor suppressor. The transactivation of different target genes differs: 10 some genes require high p53 levels, which are induced only upon exposure to p53-activating stress, whereas others are already upregulated by endogenous p53 levels. Most proapoptotic signaling pathways, including those induced by DNA damage, growth factor depletion and cytosolic calcium overload, converge on the mitochondria.…”
Section: Introductionmentioning
confidence: 99%